Behavioral Insights into Shopping Addiction: Emotional and Cognitive Drivers - Kalliampakou, Ioanna; Antonopoulou, Hera (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This paper will seek to explain the behavioral underpinnings of shopping addiction, focusing on the emotional and cognitive drivers. It has explored the prevalence and serious impact of shopping addiction and highlighted the complexity of both the emotional and cognitive elements involved in triggering and sustaining the behavior. This paper also explores the role of emotional regulation in shopping addiction and suggests potential therapeutic implications that can be derived from deeper knowledge in this respect. The treatment options proposed include behavioral interventions, such as cognitive behavioral therapy (CBT) and mindfulness-based strategies. The new approaches in the use of technology in big data analytics and virtual reality applications for understanding and intervention in shopping addiction are briefly addressed. It concludes by stating that there needs to be more research carried out on online shopping behavior and e-therapies, effective prevention strategies, and all this while considering ethical concerns in behavioral data collection. Finally, this paper synthesizes cross-disciplinary research with a view to offering an integrated insight into shopping addiction and its treatment and points out the increased applicability of technological innovations in this field.